2020
DOI: 10.1126/scitranslmed.aaw3210
|View full text |Cite
|
Sign up to set email alerts
|

An ocular glymphatic clearance system removes β-amyloid from the rodent eye

Abstract: Despite high metabolic activity, the retina and optic nerve head lack traditional lymphatic drainage. We here identified an ocular glymphatic clearance route for fluid and wastes via the proximal optic nerve in rodents. β-amyloid (Aβ) was cleared from the retina and vitreous via a pathway dependent on glial water channel aquaporin-4 (AQP4) and driven by the ocular-cranial pressure difference. After traversing the lamina barrier, intra-axonal Aβ was cleared via the perivenous space and subsequently drained to l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

12
218
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 147 publications
(233 citation statements)
references
References 84 publications
12
218
0
3
Order By: Relevance
“…Stud-ies of a glymphatic system in the optic nerve of rodents and humans have shown that tracers injected into the CSF enter the optic nerve via paravascular spaces. 6,7,10 We suggest that the main path from the CSF compartment into the visual pathway for gadobutrol is via paravascular routes, which is a prerequisite for a visual glymphatic system. 1 Furthermore, the tracer serves as a model for organic molecules with similar properties, and our findings can thus indicate impaired extravascular transport of other substances (e.g., amyloid-β).…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…Stud-ies of a glymphatic system in the optic nerve of rodents and humans have shown that tracers injected into the CSF enter the optic nerve via paravascular spaces. 6,7,10 We suggest that the main path from the CSF compartment into the visual pathway for gadobutrol is via paravascular routes, which is a prerequisite for a visual glymphatic system. 1 Furthermore, the tracer serves as a model for organic molecules with similar properties, and our findings can thus indicate impaired extravascular transport of other substances (e.g., amyloid-β).…”
Section: Discussionmentioning
confidence: 93%
“…4,5 Several studies have since supported this hypothesis. [6][7][8][9][10] In 2019, we published novel in vivo findings indicating the existence of a glymphatic system in the human visual pathway. 11 Using a magnetic resonance imaging (MRI) contrast agent (gadobutrol) as a tracer molecule, we demonstrated enrichment within the visual pathway.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…(38) measured a resistance of 5.149±1.103 mmHg/(µL/min) 241 in CD-1 wild-type mice using a similar constant-rate infusion 242 method. This higher resistance also explains their elevated 243 resting ICP (6.988±1.030 mmHg) as compared to other studies 244 with lower ICP levels (≈ 4 mmHg) (39)(40)(41). This overesti-245 mation of the resistance and resting ICP may be due to the 246 high pressure gradient established by the authors while the 247 pipette was in the brain parenchyma to assess ventricle punc-248 ture (≈ 29 mmHg).…”
mentioning
confidence: 83%
“…In the brain, another organ in the body lacking lymphatic vessels, interstitial fluid moves through the parenchyma via paravenous drainage pathways to the central nerve system (16) named the glymphatic system. A similar system has recently been described in the eye, which also lacks lymphatic vessels in the retina and optic nerve head (17). In the brain, cerebrospinal fluid is driven by arterial pulsations in the parenchyma (18).…”
Section: Regulation Of Transcapillary Fluid Fluxmentioning
confidence: 71%